Theoretical physics research developments - Sullivan, John P.; Montey, Andrew L. (Physics research and technology., 2011)
This new book presents and discusses current research developments in the study of theoretical physics. Topics discussed include dark energy as the source of the time-dependent Einstein cosmological constant; non-linear refractive index theory; quantum coherence and tunable transient behavior of a double-control four-level atomic vapor; laser prototyping of polymer-based nanoplasmonic components and radiative transitions of mesons in an independent-quark potential model.